Surface Charge Affects the Intracellular Fate and Clearance Dynamics of CdSe/ZnS Quantum Dots in Macrophages - Yuan-Yuan Liu; Yong-Yue Sun; Yuan Guo; Lu-Lu Chen; Jun-Hao Guo; Haifang Wang (Nanomaterials)
The biological effects of nanoparticles are closely related to their intracellular content and location, both of which are influenced by various factors. This study investigates the effects of surface charge on the uptake, intracellular distribution, and exocytosis of CdSe/ZnS quantum dots (QDs) in Raw264.7 macrophages. Negatively charged 3-mercaptopropanoic acid functionalized QDs (QDs-MPA) show higher cellular uptake than positively charged 2-mercaptoethylamine functionalized QDs (QDs-MEA), and serum enhances the uptake of both types of QDs via protein corona-mediated receptor endocytosis. QDs-MEA primarily enter the cells through clathrin/caveolae-mediated pathways and predominantly accumulate in lysosomes, while QDs-MPA are mainly internalized through clathrin-mediated endocytosis and localize to both lysosomes and mitochondria. Exocytosis of QDs-MPA is faster and more efficient than that of QDs-MEA, though both exhibit limited excretion. In addition to endocytosis and exocytosis, cell division influences intracellular QD content over time. These results reveal the charge-dependent interactions between QDs and macrophages, providing a basis for designing biocompatible nanomaterials.